2023
DOI: 10.14202/vetworld.2023.766-772
|View full text |Cite
|
Sign up to set email alerts
|

Causes of fetal death in the Flemish cattle herd in Brazil

Abstract: Background and Aim: Flemish cattle in Brazil are on the brink of extinction and are found only in one herd in Lages, Santa Catarina State. This study aimed to uncover the reasons for the recurring abortions in the Flemish cattle herd. Materials and Methods: Seventeen Flemish fetuses underwent postmortem examinations, with samples collected for histopathology and microbiology culture tests, polymerase chain reaction (PCR) test for Neospora caninum, and reverse transcription-PCR (RT-PCR) test for bovine viral d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Indeed, sample size limitations are common in such conditions, and in studies with native cattle breeds, as shown by others (Mastromonaco and Gonzalez-Grajales, 2020;Sunds et al, 2021). The remaining Brazilian Flemish herd is already threatened by extinction and inbreeding, and targeting available specimens to conservation programs, such as the one in France (Lauvie et al, 2008;Marian et al, 2023) and under this study, justifies efforts to better understand responses to reproductive technologies.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Indeed, sample size limitations are common in such conditions, and in studies with native cattle breeds, as shown by others (Mastromonaco and Gonzalez-Grajales, 2020;Sunds et al, 2021). The remaining Brazilian Flemish herd is already threatened by extinction and inbreeding, and targeting available specimens to conservation programs, such as the one in France (Lauvie et al, 2008;Marian et al, 2023) and under this study, justifies efforts to better understand responses to reproductive technologies.…”
Section: Discussionmentioning
confidence: 70%
“…precocity, longevity and hardiness, with the production of milk with high fat and protein contents, and good quality meat (Thaler et al, 1996;Goetten et al, 2015). Due to the small size of the breed´s population, Flemish cattle have been targeted for conservation programs in France since late 1970s (Lauvie et al, 2008), as it is considered in risk of extinction (Marian et al, 2023). In Brazil, the breed was introduced in 1912, and currently, the remaining animals from the original group comprise a pure herd of approximately 50 animals, which has not been crossed with other breeds (Alfonzo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the current endangered situation of Belgian Red Cattle has raised concerns. Lucas Marian et al showed that the Belgian Red Cattle suffers from Neisseria canis infection which may be the cause of reproductive disorders that lead to abortion in the herd [19]. The study was conducted by Lucas Marian et al We therefore focused on the signaling pathway concerning reproduction in Belgian cattle.…”
Section: Reproductive Performance Related Genesmentioning
confidence: 99%